A decentralized and secure blockchain platform for open fair data trading. (3rd December 2019) - Li, Ya‐Nan; Feng, Xiaotao; Xie, Jan; Feng, Hanwen; Guan, Zhenyu; Wu, Qianhong
Summary: As the value of data has received considerable attention, data trading shows broad market prospects. The existing data trading methods, including private trades and centralized trades, have high risks regarding transaction security and data protection. To solve this problem, we propose a decentralized trading solution for open fair data trading by deploying the smart contract on the blockchain network. The data for sale are encrypted and stored on the distributed storage platform but not directly on the blockchain network. Because the trading content is the decryption key of the data, the proposed new method can alleviate the storage pressure of the blockchain by reducing the transaction cost. We conduct a security analysis which shows that our scheme achieves secure, practical, open, and fair trading. We implement our trading contract with solidity and test it on the Ethereum's test network, and extensive experiments demonstrate desirable feasibility of our proposal.